2019
DOI: 10.1029/2018jb016526
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stress on Limestone Permeability and Effective Stress Behavior of Damaged Samples

Abstract: The evolution of permeability and its effective stress behavior is related to inelastic deformation and failure mode. This was systematically investigated in Indiana and Purbeck limestones with porosities of 16% and 14%, respectively. High-pressure compression tests were conducted at room temperature on water-saturated samples. At relatively high confinement shear-enhanced compaction was observed to initiate at a critical stress, accompanied by significant permeability reduction of up to a factor of~3. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 45 publications
(123 reference statements)
7
30
1
Order By: Relevance
“…This agreement with the normality condition motivates us to further test the postulate with two other limestones, which have recently been investigated in relation to the BDT and permeability evolution (Baud, Exner, et al., 2017; Brantut et al., 2018; Meng et al., 2019). The Purbeck limestone from England is made up of calcitic peloids (100–500 μm) in the form of micrites surrounded by sparry cement, as well as polycrystalline quartz dispersed in the aggregate.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This agreement with the normality condition motivates us to further test the postulate with two other limestones, which have recently been investigated in relation to the BDT and permeability evolution (Baud, Exner, et al., 2017; Brantut et al., 2018; Meng et al., 2019). The Purbeck limestone from England is made up of calcitic peloids (100–500 μm) in the form of micrites surrounded by sparry cement, as well as polycrystalline quartz dispersed in the aggregate.…”
Section: Discussionmentioning
confidence: 60%
“…The exterior appearance of the samples indicates shear band formation and brittle faulting. Previous studies of Indiana limestone (Meng et al., 2019; Vajdova et al., 2012) deformed to relatively large strains under similar pressures have reported band angle of ∼30°relatively to σ 1 . In contrast, at effective pressures of 30 MPa and beyond, shear‐enhanced compaction was observed to initiate at effective mean stresses lower than P* , ranging from 44 to 58 MPa (Figure 2b).…”
Section: Mechanical Datamentioning
confidence: 79%
See 1 more Smart Citation
“…The clay shell model assumes that the permeability and pore volume change both depend solely on the radius a , and accordingly their effective stress coefficients are predicted to be identical, given by κ=β=)(aPP/)(aPC. Berryman (1992) has pointed out that this is speculative, and indeed recent experiments conducted by Wang et al (2018) and Meng et al (2019) on limestones showed that the predicted equality is consistently violated, such that the value of κ can be significantly greater than that of β.…”
Section: Discussionmentioning
confidence: 99%
“…A common feature of these models (with the exception of the clay particle model) is that their determination of κ is solely based on consideration of the pore volume change, with the premise that the coefficients κ and β for permeability and pore volume change are equivalent, which Berryman (1992) pointed out to be speculative. Indeed, his theoretical analysis suggested that the two coefficients can attain quite different values, and the data of Wang et al (2018) for limestones and Meng et al (2019) for deformed limestones show β values significantly lower than κ. Is this discrepancy between the two coefficients κ and β observed also in a clayey sandstone, and if so, how can existing models be modified to more realistically capture the laboratory data?…”
Section: Introductionmentioning
confidence: 99%